PERAN SOCIAL CAPITAL DALAM MEMITIGASI PENGARUH ROLE STRESS TERHADAP JOB PERFORMANCE (Studi Kasus pada Profesi Akuntan di Kebumen, Puworejo, dan Purwokerto) - Mahardhika, Arya Samudra; Prasetyo, Anton (Universitas Nahdlatul Ulama Surabaya, 2018)
The purpose of this study was to analyze the effect of role stress consisting of role conflict and role ambiguity on job performance, and to analyze the role of social capital as a moderating variable in the relationship. Respondents from this study were accountant professions in Kebumen, Purworejo, and Purwokerto, sampling was done by purposive sampling with the criteria of the accounting profession who had worked for 1 (one) year, the sample studied was 65. The results of hypothesis testing using WarpPLS software 3.0 shows that role stress has a significant effect on job performance, but the coefficient of job ambiguity shows the opposite direction of the hypothesis. Inaddition, this study also found that social capital has a role in reducing the negative influence of role conflict on job performance, but its role cannot be proven in role ambiguity